Pengaruh Bauran Promosi terhadap Volume Penjualan Produk Tabungan JTRUST Bisnis pada Bank JTRUST Indonesia tbk Cabang Palembang - Noviar Indra; Siti Komariah Hildayanti; Omar Hendro (Integritas Jurnal Manajemen Profesional (IJMPRO), 2020)
This study entitled The Effect of Promotion Mix on Sales Volume of Jtrust Bisnis Savings Products at Bank Jtrust Indonesia Tbk Palembang Branch. This research instrument uses a questionnaire, then uses multiple linear regression to process data that has been tabulated from the results of respondents' answers. The results of the study concluded, first, the advertising variable (X1) had a positive and significant effect on sales volume (Y). Second, the sales promotion variable (X2) has a positive and significant effect on sales volume (Y). Third, public relations and publication (X3) variables have a positive and significant effect on sales volume (Y). Fourth, personal sales variables (X4) have a positive and significant effect on sales volume (Y). Fifth, the direct marketing variable (X5) has a positive and significant effect on sales volume (Y). The six advertising variables (X1), sales promotion (X2), public relations and publications (X3), personal sales (X4), direct marketing (X5) have a positive and significant effect on sales volume (Y). This means that the independent variable (X) together increases, so the sales volume (Y) increases.